2019
DOI: 10.1145/3298981
|View full text |Cite
|
Sign up to set email alerts
|

Federated Machine Learning

Abstract: Today’s artificial intelligence still faces two major challenges. One is that, in most industries, data exists in the form of isolated islands. The other is the strengthening of data privacy and security. We propose a possible solution to these challenges: secure federated learning. Beyond the federated-learning framework first proposed by Google in 2016, we introduce a comprehensive secure federated-learning framework, which includes horizontal federated learning, vertical federated learning, and federated tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
886
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 3,944 publications
(889 citation statements)
references
References 39 publications
0
886
0
3
Order By: Relevance
“…Moreover, studies have found that remote sensing data and its derived bands have good practicability for simulating forest AGC [35][36][37]; this is especially the case when combined with machine learning algorithms that allow for large scale automated analysis of high dimensional data from satellites [38]. The machine learning approach can derive rich information from remote sensing data as the input data, and continuously optimize the algorithm's performance via empirical learning to make the results more feasible and credible [39][40][41]. Remotely sensed datasets, combined with machine learning algorithms for intelligent estimation of forest AGC, support more efficient and precise observation and management of forest resources [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have found that remote sensing data and its derived bands have good practicability for simulating forest AGC [35][36][37]; this is especially the case when combined with machine learning algorithms that allow for large scale automated analysis of high dimensional data from satellites [38]. The machine learning approach can derive rich information from remote sensing data as the input data, and continuously optimize the algorithm's performance via empirical learning to make the results more feasible and credible [39][40][41]. Remotely sensed datasets, combined with machine learning algorithms for intelligent estimation of forest AGC, support more efficient and precise observation and management of forest resources [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Although the local raw data is not exposed in FL setting, FL on its own still lacks theoretical privacy guarantees [33], and may leak sensitive information about the training data [36]. Therefore, the combination of FL and proper privacy-preserving mechanisms, such as DP [14], HE [30], MPC [17], etc., is a necessity to alleviate FL's privacy risks.…”
Section: Related Workmentioning
confidence: 99%
“…Vertical federated learning (VFL) [20] has been recognized as one of the effective solutions for encouraging enterprise-level data collaborations while respecting data privacy [36], required by the strict government regulations like Europe's General Data Privacy Regulations (GDPR [34]). Unlike horizontal federated learning (HFL) [25,6] setting in which the decentralized datasets share the same feature space but little intersection on the sample space, in VFL setting, the datasets of different organizations share the same or similar sample space but differ in feature space.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations